PENINGKATAN HASIL BELAJAR TEMA 7 INDAHNYA KERAGAMAN DI NEGERIKU DENGAN MENGGUNAKAN MEDIA VIDIO PEMBELAJARAN - Afdhal Qudri; Ratna Sari Dewi; Encep Andriana (Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this study is to improve the learning outcomes of fourth grade students of SD Negeri 19 Sijuk. The theme of the beauty of diversity in my country by using learning video media in 2021. The research subjects in this study were fourth grade students of SD Negeri 19 Sijuk with a total of 29 students with details of 15 male and 14 female. This research was conducted in three cycles. Data analysis used test and observation techniques. In the first cycle of students who completed as many as 17 students or 58.62%, in the second cycle to 20 students or 68.96%, and in the third cycle to 24 students or 82.75%. Increased observation results In the first cycle is quite sufficient with the acquisition of a score of 58 out of 116 or a value of 2 in quantitative, then the observation results in the second cycle are classified as good with the acquisition of a score of 72 out of 116 or a score of 2.48 in quantitative, then the observation results in the third cycle are classified as good with the acquisition of a score of 91 out of 116 or a value of 3.17 in quantitative. Thus, it can be concluded that the application of learning video media can improve the learning outcomes of fourth grade students of SD Negeri 19 Sijuk. The theme of the beauty of diversity in my country. So the researchers suggest that learning video media be applied to learning the theme of the beauty of diversity in my country.